Involvement of the CD95 (APO-1/Fas) receptor/ligand system in drug-induced apoptosis in leukemia cells - Friesen, Claudia; Herr, Ingrid; Krammer, Peter H.; Debatin, Klaus-Michael (Nature medicine, 1996)
Cytotoxic drugs used in chemotherapy of leukemias and solid tumors cause apoptosis in target cells1,2. In lymphoid cells the CD95 (APO-1/Fas)/CD95 ligand (CD95-L) system is a key regulator of apoptosis3-6. Here we describe that doxorbicin induces apoptosis via the CD95/CD95-L system in human leukemia T-cell lines. Doxorubicin-induced apoptosis was completely blocked by inhibition of gene expression and protein synthesis. Also, doxorbicin strongly stimulated CD95-L messenger RNA expression in vitro at concentrations relevant for therapy in vivo. CEM and Jurkat cells resistant to CD95-mediated apoptosis were also resistant to doxorbicin-induced apoptosis. Furthermore, doxorbicin-induced apoptosis was inhibited by blocking F(ab′)2 anti-APO-1 (anti-CD95) antibody fragments. Expression of CD95-L mRNA and protein in vitro was also stimulated by other cytotoxic drugs such as methotrexate. The finding that apoptosis caused by anticancer drugs may be mediated via the CD95 system provides a new molecular insight into resistance and sensitivity toward chemotherapy in malignancies.
Gesehen am 21.10.2024